ANALYSIS OF VALUE CREATED PRODUCT STRATEGIES ON IMPROVING BUSINESS COMPETITIVENESS - Banuara Nadeak; Reminta Lumban Batu (Jurnal Ekonomi dan Manajemen, 2020)
The condition of Karawang as a national rice barn has now shifted to industrialization and supporting cities for the Capital City and has received poor ratings because it is a city with a high ranking of poor people. These problems can be solved by increasing MSME activities in various fields. The sustainability of MSME is very important because it supports the growth of big business and is able to provide benefits for regional economic growth. Implementation of value creation strategies in an effort to improve business activities carried out as a strategy at the corporate and business level. The application of value creation that focuses on internal resources owned is also related to the competitiveness strategy in an effort to increase the competitiveness of a company or a business. This study was designed to find out how product strategies that create values ​​when faced with business competitiveness in efforts to improve the economy of the poor. This study uses a cross sectional method through descriptive verification methods with testing path analysis using SPSS. Comparative testing is carried out to determine the comparison of consumer behavior between platforms / websites.